2023
DOI: 10.15294/jpii.v12i1.39941
|View full text |Cite
|
Sign up to set email alerts
|

Biology Students' Science Literacy Level on Genetic Concepts

Abstract: Scientific literacy is one’s scientific knowledge to apply based on scientific problems. It is important for shaping generational readiness to face the challenges of the 21st century. Scientific literacy is necessary for learning Biology because it can support skills in identifying, explaining scientific phenomena, and generalizing scientific facts. However, the scientific literacy level of students in Indonesia is still relatively low, ranking 70th out of 79 countries with an average achievement of 396. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, research shows that students' science literacy skills, particularly in biology, are still relatively low in various educational environments, including universities and primary schools in Indonesia [1], [7], [12], [13]. This low level of science literacy can be caused by several factors such as ineffective teaching methods, lack of contextual learning, and misconceptions among students [5]. To address this problem, efforts are being made to improve science literacy through various approaches, including the use of scientific methods in the learning process, the development of teaching modules, and the implementation of innovative learning models that emphasize contextual learning and readability.…”
Section: Science Literacy In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research shows that students' science literacy skills, particularly in biology, are still relatively low in various educational environments, including universities and primary schools in Indonesia [1], [7], [12], [13]. This low level of science literacy can be caused by several factors such as ineffective teaching methods, lack of contextual learning, and misconceptions among students [5]. To address this problem, efforts are being made to improve science literacy through various approaches, including the use of scientific methods in the learning process, the development of teaching modules, and the implementation of innovative learning models that emphasize contextual learning and readability.…”
Section: Science Literacy In Educationmentioning
confidence: 99%
“…However, the current level of scientific literacy among students is relatively low, indicating the need for improvement [3], [4]. Various techniques and models, such as Lesson Study and Problem-Based Learning, have been shown to effectively enhance students' scientific literacy skills [5]. By implementing these approaches, educators can equip students with the ability to find, evaluate, and effectively use information, enabling them to navigate the complexities of the 21st century with confidence and competence.…”
Section: Introductionmentioning
confidence: 99%